1
by alezandraagreg

• Brainly User
2015-10-02T14:38:01+08:00
1)  x/2 - (2y)/3 = 12
Transform to equation of the line in standard form ax + by = c
LCD: (2) (3)
(3)(2)x - (2)(3)(2y)  = 12 (2)(3)
2            4

3x - 4y = 72,  Equation 1

2) x/5 + 2y = 4
Transform to equation of the line in standard form:
LCD:  5
5x + (5) (2y) = (5)(4)
5

x + 10y = 20
x = -10y + 20, Equation 2

3)  Substitute - 10y + 20 in Equation to for x in Equation 1.

3(-10y + 20) - 4y = 72
-30y + 60 - 4y = 72
-30y - 4y = 72 - 60
-34y = 12

-34y = 12
- 34     -34

y = -12/34 or -6/17
y = -6/17

4)  Subsitute -6/17 for y in Equation 2 (x = -10y + 20)

x = -10 (-6/17) + 20
x = 60/17 + 20
LCD:  17

x = 60  +  340
17       17
x = 400/17

x = 400/17                           y = -6/17

To check:

x/2 - (2y)/2 = 12
400/17 - 2 (-6/17) = 12
2             3
(400/17) (1/2) - (-12/17)(1/3) = 12
400/34  + 4/17 = 12
200/17 + 4/17 = 12
204/17 = 12
12 = 12

x/5 + 2y = 4
400/17 + 2(-6/17) = 4
5
(400/17) (1/5) - 12/17) = 4
80/17 - 12/17 = 4
68/17 = 4
4 = 4